Pengembangan Media Moral Card Dalam Pembelajaran PAI di SMP Negeri 1 Rantau Selamat Kabupaten Aceh Timur - Refo, Afrizal; Alam, Muhammad Ridho; Muhammaddar (Program Studi Pendidikan Agama Islam, 2025)
This research aims to: (1) develop Moral Card Media in PAI learning for class VIII students at SMPN 1 Rantau Selamat, East Aceh Regency. The results of this development are feasible and good to use, (2) To determine the level of feasibility and practicality of this Moral Card media in PAI learning at SMP Negeri 1 Rantau Selamat, East Aceh Regency. This research uses the Research and Development (R&D) method and the model used in the Moral Card media development process uses the ADDIE development model through 5 stages including (1) Analysis, (2) Design, (3) Development, (4) Implementation, ( 5) Evaluation. The subjects of this research include lecturers who are media experts and material experts, as well as class VIII students at SMP Negeri 1 Rantau Selamat and also PAI subject teachers. The research object is moral cards in PAI learning. The instruments used to assess the suitability of the moral card include an assessment sheet for the suitability of material experts and media experts, and a practicality assessment sheet in the form of a questionnaire on PAI student and teacher responses to the moral card. Feasibility testing was carried out by two teams of experts, namely, media experts and material experts, the results were tested for practicality on class VIII students of SMP Negeri 1 Rantau Selamat. The results of the feasibility study showed that the media expert validation was 93%, the material expert was 89.47%, and the practicality test on class VIII students of SMP Negeri 1 Rantau Selamat got an average of 86.18%, and the teacher response was 95%. Therefore, this research succeeded in developing learning media in the form of digital-based Moral Cards in PAI learning in the material CHAPTER 7 Believing in the Prophets and Apostles of Allah to be a Digital Generation with Character that is suitable and practical to use as independent teaching material for class VIII students of SMP Negeri 1 Rantau Selamat.